Obstetrics and gynaecology postgraduate training in Malaysia: training curriculum - Omar, Siti Zawiah; Ismail, Hamizah; Ismail, Mohd Pazudin; Abdul Ghani, Nur Azurah; Jeganathan, Ravichandran; Shafie, Zaridah; Kar Koong, Carol Lim; Suharjono, Harris Njoo; Omar, Mohd Hashim; Hamdan, Mukhri; Luk Tien Wee, Lucas (Majlis Dekan Fakulti Perubatan Universiti Awam Malaysia MERDU, 2021)
This document is National Postgraduate Medical Curriculum, (NPMC), for Obstetrics and Gynaecology, (O&G), and is a collaboration between the O&G Conjoint Board of the Malaysian National Universities, Ministry of Education (MOE), and the Ministry of Health Malaysia, (MOH). It provides a structured and unified curriculum for the training of Obstetrics and Gynaecology specialists throughout the country, in alignment with the national strategy for healthcare. It is the common curriculum for all postgraduate training pathways for Obstetrics and Gynaecology. The committee included academicians and senior consultants from the respective Universities, Ministry of Health and Academy of Medicine. Members from alumni also contributed in designing this curriculum. This training programme has been designed to facilitate the attainment of knowledge, clinical skills, professional values and behaviours that are required to practice with a holistic approach to medicine. It is to ensure that consistent and high standards are met so as to produce Obstetricians and Gynaecologists who are highly knowledgeable, practice good ethics and provide high standards of clinical practice.